ANALISIS STATUS MUTU AIR SUNGAI KOTA BOGOR TAHUN 2015-2019 BERDASARKAN SEGMENTASI DAN MUSIM - Nasution, Lailatussyifah; Darundiati, Yusniar Hanani; Suhartono, Suhartono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The development of Bogor city as a buffer zone for the capital has made its water quality decrease. The river water quality has never reached the Water Quality Index (WQI) set for 2015-2019. This study aims to analyze the difference of Bogor river water quality value in 2015-2019 based on segmentations and seasons. Storet and Pollution Index method were used to measure the value of the quality status. Based on statistical tests results, the value between upstream, middle, and downstream both in rainy (p value = 0,252 for Storet method, p value = 0,520 for Pollution Index method) and dry seasons (p value = 0,817 for Storet method, p value = 0,230 for Pollution Index method) did not differ significantly. The value based on Storet method between rainy and dry seasons differed significantly, both in upstream (p value = 0,008) and middlestream (p value = 0,001) but did not differ significantly in downstream (p value = 0,066). Based on Pollution Index method, the value between rainy and dry seasons did not differ significantly in upstream (p value = 0,961) but differed significantly in middlestream (p value = 0,028) and downstream (p value = 0,031). BOD, total phosphate, and nitrite were dominant parameters for quality status based on segmentations, while coliform were dominant parameters for quality status based on seasons. It can be concluded that the value of water quality status in Bogor city between upstream, middle, and downstream do not differ significantly and tends to be worse in dry season.